2018
DOI: 10.1016/j.semnephrol.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The Warburg Effect in Diabetic Kidney Disease

Abstract: Summary Diabetic kidney disease (DKD) is the leading cause of morbidity and mortality in diabetic patients. Defining risk factors for DKD using a reductionist approach has proven challenging. Integrative omics-based systems biology tools have shed new insights in our understanding of DKD and have provided several key breakthroughs for identifying novel predictive and diagnostic biomarkers. In this review, we highlight the role of the Warburg effect in DKD and potential regulating factors such as sphingomyelin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 85 publications
(116 reference statements)
4
76
1
Order By: Relevance
“…Additionally, glycolysis inhibition ameliorated kidney pathology in an animal model of polycystic kidney disease (33). Aberrant glycolysis similar to the Warburg effect, which is characteristics of tumor cell metabolism, has been a focus in the pathogenesis of DKD (34); to date, there has been no clear demonstration of the link between inhibition of aberrant glycolysis and SGLT-2 inhibitor use in human DKD. As discovered in the current study, direct effects of SGLT-2 inhibition on proximal tubule glycolysis and EMT could play significant roles Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, glycolysis inhibition ameliorated kidney pathology in an animal model of polycystic kidney disease (33). Aberrant glycolysis similar to the Warburg effect, which is characteristics of tumor cell metabolism, has been a focus in the pathogenesis of DKD (34); to date, there has been no clear demonstration of the link between inhibition of aberrant glycolysis and SGLT-2 inhibitor use in human DKD. As discovered in the current study, direct effects of SGLT-2 inhibition on proximal tubule glycolysis and EMT could play significant roles Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our recent study found that cyclin G2 expression plays an important role in controlling glioma progression by regulating proliferation and the Warburg effect via its interaction with lactate dyhydrogenase A (LDHA) . Additionally, other studies have provided unbiased evidence that the Warburg effect plays a pivotal role in the development of diabetes . These lines of evidence suggest that cyclin G2 may be involved in the pathological processes related to diabetes.…”
Section: Introductionmentioning
confidence: 93%
“…Present experiments further explored the protective effect of Pyr on HK‐2 cells under the HG condition. There are some aberrant factors causing renal injury in diabetes, such as abnormal glucose metabolism with Warburg phenomenon and dysfunction of mitochondria in glomerular endothelial and tubular epithelial cells, as well as advanced glycation end products [2,23]. In recent studies in diabetes, ER stress has been a major area of interest [24].…”
Section: Discussionmentioning
confidence: 99%